PERANCANGAN APLIKASI PROMOSI DAN PENJUALAN PRODUK BERBASIS WEBSITE PADA TOKO BAJU WEARSAREY - Kevin Lukas; Desi Arisandi; Tji Beng Jap (Fakultas Teknologi Informasi Universitas Tarumanagara, 2024)
The Planning of a Promotion and Sales Application for a Website-Based Product at Wearsarey Clothing Store aims to enhance the quality of Wearsarey's clothing store business in sales activities. The development of this website-based application also aims to facilitate customers in conducting transactions and obtaining information about the products sold by Wearsarey clothing store. The design of this application uses the System Development Life Cycle (SDLC) methodology with a waterfall model. The database used in this application is MySQL. The programming languages used are HTML and PHP.